Efficacy and safety of short-pulse erbium: Yttrium aluminum garnet laser treatment of Becker’s nevus in Saudi patients: A pilot study - Al-Saif, Fahad; Al-Mekhadab, E.; Al-Saif, H. (International Journal of Health Sciences, 2017)
Objective: Becker’s nevus (BN) is a benign cutaneous hamartoma. Although different types of lasers have been used to treat the pigmentary part of BN, to date, no definite treatment modality has been determined. The objective of this study is to evaluate the efficacy and safety of erbium: yttrium aluminum garnet (Er: YAG) laser treatment among Saudi patients with BN. Patients and Methods: A series of 10 patients (skin phototypes III-V) with BN underwent treatment with an Er: YAG laser. Biopsies were taken from all patients to confirm the diagnosis. Treatment consisted of using a 2940 nm Er: YAG laser (fluence 700 mj/cm2, short pulse, 3 mm spot size). Each patient underwent one session with three to five passes (the endpoint of passes was pinpoint bleeding). Clinical outcome was assessed using digital photographic method, before each treatment session and after the final visit. Clinical assessment scores were determined at each follow-up visit. Results: Seven patients completed the study. All patients noticed a significant reduction in pigmentation. Five of the patients had good improvement, and the remaining two had moderate improvement. The mean reepithelialization time was 7 days, and post-treatment erythema was seen in all patients (mean follow-up of 6 weeks). Post-inflammatory hypopigmentation was observed in all patients. No untoward sequelae were observed during the study or follow-up period. Conclusion: Er: YAG laser therapy can be an efficient modality for reducing the pigmentary part of BN. No scar formation, significant dyspigmentation, or recurrences were observed after 1 year.